2022
DOI: 10.5435/jaaos-d-21-00920
|View full text |Cite
|
Sign up to set email alerts
|

Movement Is Life—Optimizing Patient Access to Total Joint Arthroplasty: Cardiovascular Health Disparities

Abstract: Cardiovascular disease includes a collection of conditions with 6.7% of American adults having coronary artery disease and 45% having hypertension. Proper management of these conditions is low (<25%). Hypertension is highest among African Americans and is associated with lower socioeconomic status and education level. Heart disease is associated with postoperative complications, such as cardiovascular and cerebrovascular events, pulmonary and coagulopathy complications, and mortality. Underserved communities c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Patients with CVD will likely have questions related to medication regimens and uncertainty about how they should adjust these regimens prior to TJA. Current guidelines that nurse navigators should be familiar with and be prepared to discuss with PCPs and cardiologists include that hypertension medications such as β-blockers, angiotensin II receptor blockers (ARBs), and angiotensin-converting enzyme (ACE) inhibitors can be continued perioperatively, as can statins or aspirin taken for cardiac protection (American College of Surgeons, 2017; Fleisher et al, 2014; Wiznia, Santos, et al, 2022). In addition, continuation of anticoagulants and nonsteroidal anti-inflammatory agents in the 2 weeks prior to TJA should be discussed with the patient's PCP or cardiologist (American College of Surgeons, 2017; Fleisher et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with CVD will likely have questions related to medication regimens and uncertainty about how they should adjust these regimens prior to TJA. Current guidelines that nurse navigators should be familiar with and be prepared to discuss with PCPs and cardiologists include that hypertension medications such as β-blockers, angiotensin II receptor blockers (ARBs), and angiotensin-converting enzyme (ACE) inhibitors can be continued perioperatively, as can statins or aspirin taken for cardiac protection (American College of Surgeons, 2017; Fleisher et al, 2014; Wiznia, Santos, et al, 2022). In addition, continuation of anticoagulants and nonsteroidal anti-inflammatory agents in the 2 weeks prior to TJA should be discussed with the patient's PCP or cardiologist (American College of Surgeons, 2017; Fleisher et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…26 They may require additional care both before and after their surgery to ensure a successful outcome, such as more extensive preoperative medical optimization, a longer hospital stay, or a discharge to a skilled nursing facility. 6,[27][28][29][30] This increased comorbidity burden among some minorities is likely a notable contributor to racial disparities in postoperative complication rate-a 2021 study found that race was not an independent risk factor of 30-day complications for total knee arthroplasty after controlling for comorbidities. 31 The gaps in applicability of the JC process measure to the needs of more socially vulnerable populations with greater comorbidity burden may explain the discrepancy in our findings between the CMS and JC analyses.…”
Section: Discussionmentioning
confidence: 99%
“…35 Similarly, process measures could be adjusted or introduced to evaluate preoperative patient optimization with a specific focus on social determinants of health, such as food access, health literacy, and utilization of social safety net and community resources. 29,30 Additional studies are needed to assess the viability of these proposed policy solutions.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, CRP was directly related to periprosthetic infections in orthopedic patients and was found to be the most specific marker (87.10%). [24][25][26] Nevertheless, other parallel causes for an elevated CRP value, especially in elderly patients, should be excluded during hospitalization. Among the pre-diseases described above, arterial hypertension, renal insufficiency, aspirin intake and COPD were shown to be associated with the occurrence of systemic complications.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies underlined an increased risk of complications in connection with cardiovascular and renal pre-diseases of the patients. 24,25 Therefore, in preoperative planning, increased attention should be paid to a well-controlled arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%